PERANCANGAN SISTEM INFORMASI AKADEMIK DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) BERBASIS WEB (STUDI KASUS SMP GEMILANG MODERNLAND) - Muhamad Yasser Arafat (CV. Multi Kreasi Media, 2022)
The need for information in the field of education is crucial in determining the progress of an institution. With the utilization and application of information technology, data sets can be interconnected. The Academic Information System at SMP Gemilang Modernland is an academic information system that must be implemented for easier access by students, teachers, school administrators, and the wider community seeking information about the school. The delivery of information, such as teacher data, student data, class representatives, school information, payments, and classes, is currently not as efficient as desired, resulting in the accumulation of data that requires a considerable amount of time to process. To address these challenges, a system is required. The system is designed using the PHP programming language with a MySQL database and employs the Rapid Application Development (RAD) method. The outcome of this research is a web-based academic information system that is needed by teachers, students, staff, and external communities, enabling easy and swift access without constraints of time and place.